Supporting first-time parents in their homes: an informal setting enabling interprofessional collaboration - Cecilia Franzén; Eva-Lotta Nilsson (BMC, 2024)
Abstract Background Home visiting programmes aiming to support parents and promote more equal health amongst young children have grown in Sweden and in other countries. These programmes involve interprofessional teams. Teamwork in interprofessional contexts often requires setting boundaries, but professionals' boundary work in the home setting is unexplored. Therefore, this article focuses on interprofessional teams comprising child healthcare nurses, midwives, social workers, and dental hygienists in a home visiting programme for first-time parents in Sweden; it aims to explore how the professionals performed boundary work that enabled collaboration and to investigate important contextual conditions for this kind of boundary work. Methods The data were drawn from semi-structured interviews with twelve professionals from the four different disciplines. Content analysis was used to explore their boundary work. Results The findings show that the professionals performed three forms of collaborative boundary work. They maintained boundaries by clarifying their distinct roles and expertise. However, the differences were viewed as complementary, and the professionals worked together humbly to complement each other's knowledge and perspectives. Lastly, they tended to drop perceptions of prestige and blurred the boundaries to accommodate their overlapping knowledge. Important conditions for the success of collaborative boundary work were meetings prior to the home visits, the opportunities for discussion and reflection after the home visits, and the informal character of the home setting. Consequently, the professionals were able to jointly contribute to a holistic view of the visited families, which increased the possibilities to meet these families' needs. Conclusions This study contributes knowledge on boundary work in interprofessional collaborations in the home setting. The informal character of the home setting seemed to facilitate collaboration and contributed to creating informal professional roles. The findings suggest that having interprofessional teams in the home setting enabled collaboration as well as reinforced support for first-time parents, which emphasizes the merit of home visit programmes.